2011
DOI: 10.5194/acp-11-4105-2011
|View full text |Cite
|
Sign up to set email alerts
|

Emission inventory of anthropogenic air pollutants and VOC species in the Yangtze River Delta region, China

Abstract: Abstract. The purpose of this study is to develop an emission inventory for major anthropogenic air pollutants and VOC species in the Yangtze River Delta (YRD) region for the year 2007. A "bottom-up" methodology was adopted to compile the inventory based on major emission sources in the sixteen cities of this region. Results show that the emissions of SO 2 , NO x , CO, PM 10 , PM 2.5 , VOCs, and NH 3 in the YRD region for the year 2007 are 2392 kt, 2293 kt, 6697 kt, 3116 kt, 1511 kt, 2767 kt, and 459 kt, respe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
182
4
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 310 publications
(200 citation statements)
references
References 37 publications
10
182
4
1
Order By: Relevance
“…The uncertainty and VOC emission estimated in the YRD region and China from different studies are presented in Table 6. Our findings were lower than those reported by Fu et al (2010), , and Wu et al (2016) but larger than those reported by Huang et al (2011). The results vary because of the different source classifications and areas covered in these studies.…”
Section: Uncertainty Analysiscontrasting
confidence: 57%
See 1 more Smart Citation
“…The uncertainty and VOC emission estimated in the YRD region and China from different studies are presented in Table 6. Our findings were lower than those reported by Fu et al (2010), , and Wu et al (2016) but larger than those reported by Huang et al (2011). The results vary because of the different source classifications and areas covered in these studies.…”
Section: Uncertainty Analysiscontrasting
confidence: 57%
“…Basing on the emission inventory of China, a previous study determined that industrial and domestic solvent use contributed 28.6% to the total NMVOC (are identical to VOCs, but with methane excluded) emission in China (Wei et al, 2008), and Shandong, Jiangsu, Guangdong, and Zhejiang were the provinces with the highest VOC emissions (Qiu et al, 2014a;. The inventory of VOCs in the YRD for 2007 also illustrated that industrial sources, including fuel combustion facilities and non-combustion processes, contribute roughly 69% of the total VOC emissions (Huang et al, 2011). Although significant progress was achieved in estimating VOC emissions and characterizing the spatiotemporal variations over the YRD region, some limitations persist.…”
Section: Introductionmentioning
confidence: 99%
“…Solvent use including painting and printing processes has been recognized as important emission source of volatile organic compounds (VOCs) in the atmosphere (Na et al, 2003;Liu et al, 2008a;Guo et al, 2011;Huang et al, 2011). The anthropogenic emission of VOCs in China was 20.1 Tg in 2005, and the industrial and domestic solvent use was the largest emission source accounting for 28.6% of the total VOCs (Wei et al, 2009(Wei et al, , 2011.…”
Section: Introductionmentioning
confidence: 99%
“…According to the VOC emissions inventory by Huang et al (2011), solvent use, i.e., architecture paint and auto paint, accounted for 25% of the total VOC emission of Shanghai in 2007. From the result of the source apportionment by receptor model, solvent use and production contributed around 32% of the measured ambient VOCs during 2007 to 2010 (Cai et al, 2010), while a contribution of 20% was reported by Wang et al (2012) during the 2010 Shanghai World Expo.…”
Section: Introductionmentioning
confidence: 99%
“…2(b)). Previous studies have demonstrated a considerable amount of VOC emissions contributed to solvent use and industrial production in YRD, which could be the major source of aromatics in that region (Huang et al, 2011;Wang et al, 2014). The alkene concentration, which is the sum of ethene and propene concentrations, varied dramatically from sub-ppb to a few ppb in both summers.…”
Section: Overview Of the Observed Vocsmentioning
confidence: 99%